1988
DOI: 10.1080/02678298808086395
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the rotational viscosity of ferroelectric liquid crystals based on a simple dynamical model

Abstract: Rotational viscosity and spontaneous polarization are the most important properties of a ferroelectric liquid crystal with regard to its switching time in surface stabilized or a x . field stabilized displays. Whereas there is an abundant literature about spontaneous polarization, only a few attempts have been made to determine the rotational viscosity. We set up a model for the electric response of a ferroelectric liquid crystal cell on application of an electric field. For the application of a triangular wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…The positions and configurations of the double bonds are chosen according to the half-ring notation shown in this figure. The configuration of the unsaturated carboncarbon double bond was confirmed by H NMR spectroscopy-the trans-olefinic coupling constants (z [12][13][14][15][16][17][18] Hz) are larger than those of the corresponding cis-olefinic coupling constants (z 7-1 1 H z b a n d by infrared spectroscopy, monitoring the trans absorption at 97&960cm-' and the cis absorption at 730-675cm-' [S].…”
Section: The Materialsmentioning
confidence: 97%
“…The positions and configurations of the double bonds are chosen according to the half-ring notation shown in this figure. The configuration of the unsaturated carboncarbon double bond was confirmed by H NMR spectroscopy-the trans-olefinic coupling constants (z [12][13][14][15][16][17][18] Hz) are larger than those of the corresponding cis-olefinic coupling constants (z 7-1 1 H z b a n d by infrared spectroscopy, monitoring the trans absorption at 97&960cm-' and the cis absorption at 730-675cm-' [S].…”
Section: The Materialsmentioning
confidence: 97%
“…These were measured using the electric field reversal method [6], P, measured from the integral of the induced current pulse on switching, and y measured from the current pulse profile. It was found that the dye had little effect on the spontaneous polarization of SCE 13 and ZLI4237 (no more than 2 per cent), while that of Felix 007 was raised by 1 nC cm-* (at 30°C: 12 per cent, see figure 3), and lowered in Felix010/1 by 2 n C~m -~ (at 30°C: 15 per cent).…”
Section: Spontaneous Polarization and Rotational Viscositymentioning
confidence: 99%
“…where 0 is the tilt angle and the rotational viscosity y refers to the rotation about an axis perpendicular to n and P, [6]. Equation (1) describes the reorientation of the director in the bulk of the sample and disregards the coupling of the director and the spontaneous polarization with the cell boundaries, which can lead to several surface stabilized geometries other than the uniform bookshelf geometry [7].…”
Section: Smectic C Compoundsmentioning
confidence: 99%